2015
DOI: 10.1074/jbc.m114.611798
|View full text |Cite
|
Sign up to set email alerts
|

Trans-regulation of Syndecan Functions by Hetero-oligomerization

Abstract: Background: Syndecans form non-covalently linked homodimers through their highly conserved transmembrane domains. Results: Syndecan-2 and -4 exhibit heteromolecular interaction, and this interaction regulates syndecan-mediated cellular functions. Conclusion: Hetero-oligomerization produces distinct syndecan functions. Significance: Our finding offers new insights into the underlying signaling mechanisms of syndecans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…Because this TMD also mediates heteromeric interactions of syndecans, we investigated whether Phe-169 could regulate SDS-resistant heterodimer formation. Consistent with a previous report (19), we found that wild-type syndecan-2 (SDC2) and a syndecan-4 mutant (4eTC) formed SDS-resistant heterodimers, whereas the S2(F169Y) mutant showed reduced SDS-resistant heterodimer formation with 4eTC compared with the S2(F172Y) mutant or SDC2 wild type (Fig. 1C).…”
Section: Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…Because this TMD also mediates heteromeric interactions of syndecans, we investigated whether Phe-169 could regulate SDS-resistant heterodimer formation. Consistent with a previous report (19), we found that wild-type syndecan-2 (SDC2) and a syndecan-4 mutant (4eTC) formed SDS-resistant heterodimers, whereas the S2(F169Y) mutant showed reduced SDS-resistant heterodimer formation with 4eTC compared with the S2(F172Y) mutant or SDC2 wild type (Fig. 1C).…”
Section: Resultssupporting
confidence: 81%
“…The Conserved Phenylalanine Regulates SDS-resistant Heterodimer Formation of Syndecan-2-We have reported previously that syndecan-2 and -4 formed SDS-resistant heterodimers through the GXXXG motif in their TMDs (19) and that the unique phenylalanine (Phe-167) on the TMD of syndecan-2 strengthened its homodimerization (27). In addition to Phe-167, the syndecan-2 TMD contains additional phenylalanines near the GXXXG motif.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations